DAMPAK REKRUTMEN SISTEM EMPLOYEE REFERRAL DALAM MEMBANGUN LOYALITAS KARYAWAN BARU DI SEKTOR PERBANKAN - Mulyadi Maswir; Iskandar Iskandar; Yogie Rahmat (Jurnal Ekonomi Bisnis Kompetif, 2026)
The high employee turnover rate among new employees in the first year of employment is one of the critical challenges of human resource management today. This study aims to empirically test the impact of the Employee Referral program (internal recommendation) on the loyalty of new employees in the banking sector. Using a causal associative quantitative approach, data were collected through a Likert-scale structured questionnaire from 60 respondents who were new employees from the referral recruitment channel. The sampling technique used was purposive sampling, and the data were analyzed using a simple linear regression method assisted by SPSS software. The results of the hypothesis testing (t-test) showed that the Employee Referral program had a positive and significant effect on the loyalty of new employees. The results of the coefficient of determination analysis (R2) confirmed that this internal recommendation program contributed 41.5% to the variation in loyalty of new employees. These findings theoretically support the concepts of Realistic Job Preview Theory and Social Exchange Theory, where the accuracy of pre-employment information and positive moral burden can accelerate adaptation while building affective commitment. Practically, this study recommends that HR formalize the referral system digitally while maintaining selection objectivity to secure loyalty from the initial recruitment stage